The impact of investment, PDRB growth, and minimum wage on regional tax revenue across 34 provinces in Indonesia - Sagala, Eliza Clara Yeremia (Educoretax, 2024)
Regional Tax commonly dominated Local Own-Source Revenue (PAD) from 2018 to 2023. In fact, regional tax revenue reached 73.4% of total PAD in 2023. This highlights the importance of optimizing Regional Tax collection. This study aims to determine the influence of Gross Regional Domestic Product (PDRB), Domestic Investment (PMDN), and Regional Minimum Wage (UMR) on Regional Tax Revenue. This research uses quantitative associative method with multiple linear regression to determine the relationship of dependent and independent variables. The results show that all three independent variables affect regional tax revenue simultaneously. Partially, PDRB and PMDN have a significant positive effect while Regional Minimum Wage has no significant effect on Regional Tax. This indicates that local governments must increase Gross Regional Domestic Product and Domestic Investment to optimize Regional Tax revenue. It is recommended that local governments formulate policies to encourage investment through financial incentives such as tax reductions and bureaucratic simplification, including streamlined licensing processes.